2009
DOI: 10.1007/s10522-009-9216-4
|View full text |Cite
|
Sign up to set email alerts
|

Telomere dynamics during replicative senescence are not directly modulated by conditions of oxidative stress in IMR90 fibroblast cells

Abstract: The replicative lifespan of many cell types is determined by the length of telomeres in the initiating cell population. In 20% oxygen, IMR90 cells have a shorter replicative lifespan compared to that achieved in conditions that lower the levels of oxidative stress. We sought to address the role of telomere dynamics in determining the replicative lifespan of IMR90 cells. We analysed clonal populations cultured in parallel in 3 and 20% oxygen. We observed that, at senescence, telomere length was shorter in 3% ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 45 publications
0
24
1
Order By: Relevance
“…, 1995), although contradictory results have been published on this matter (von Zglinicki et al. , 2000; Britt‐Compton et al. , 2009).…”
Section: Discussionmentioning
confidence: 99%
“…, 1995), although contradictory results have been published on this matter (von Zglinicki et al. , 2000; Britt‐Compton et al. , 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Liang et al reported that aging increases the susceptibility of MSCs to ROS and impairs their therapeutic potency [35]. Britt-Compton et al indicated that more intense ROS-generating stressors can induce senescence through the generation of telomere-independent DNA damage [36]. It has been reported that an antioxidant is an indicator inhibiting oxidative stress [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Mammalian cells cultured in 21% oxygen enter replicative senescence with longer telomeres and at earlier population doublings compared to cells grown in the presence of antioxidants or in 2% oxygen atmosphere (Chen et al ., 1995; von Zglinicki et al ., 2000; Betts et al ., 2008; Britt-Compton et al ., 2009). The cause for skin fibroblast senescence in either oxygen tension is telomere dysfunction (d'Adda di Fagagna et al ., 2003; Gire et al ., 2004; Herbig et al ., 2004).…”
Section: Discussionmentioning
confidence: 99%